Letter to Jane Tolmach; from Louis R. Nash - Louis R. Nash:::::: (1968)
The letter is a cordial invitation for Tolmach to participate in a meeting of the Oxnard Rotary Club which will be held at the Camarillo State Hospital on January 30, 1968. The time of this event will be 12 noon in the Employees Dining Room.